The Effect of Medical Theraphy on Plasma Homocysteine Levels and Carotid Intima-Media Thickness in Parkinson's Disease - Yasemin, Kaya; Fahriye, Feriha Özer; Ali, Bekir Kurt; Sema, Nur Ayyıldız; Tuba, Özcan; Esra, Yancar Demir; Tevfik, Noyan (Journal of Neurological Research And Therapy, 2016)
Objective: We aimed to investigate homocysteine levels and carotid intima-media thickness (CIMT) in Parkinson’s Disease (PD), to determine relationship of these parameters and as well as to determine whether CIMT in patients with PD was associated to age, disease duration, age of disease onset, stage, the Unified Parkinson Disease rating scale (UPDRS), the drugs used in therapy. Methods: The study population consisted of 55 PD patients (37 male) and 25 healty subjects. The severity of neurological impairment was assessed with UPDRS and the Hoehn-Yahr scale. CIMT and homocysteine levels were measured. Anti-parkinsonian treatments were recorded and the total daily dose of levodopa was calculated for each patient. Results:  Homocysteine levels were significantly higher in the patient group compared to the control group (p=0.002). A positive correlation was found between CIMT and homocysteine  (r=0.29 p=0.03), but   no a relationship between CIMT and UPDRS scores, disease duration, age of disease onset, and stage. Mean levodopa dosage did not predict CIMT 0.6 mm (AUC: 0.546, 95%CI 0.372-0.720, p=0.59). Homocysteine 14 µmol/l predicted CIMT 0.6 mm with 64% sensitivity and 69% specificity (AUC: 0.654, 95%CI 0.488-0.819, p=0.07). Dıscussion: This study revealed that homocysteine levels in levodopa + dopa decarboxylase enzyme inhibitor (DDEI) group were increased which was correlated with a mild increasement of CMIT. This might indicate to the importance of clinical and radiological follow up of PD patients who are under treatment of levodopa + DDEI. Conclusion: Our Findings May Suggest The Role Of CIMT As A Meaningful Clinical Marker For Follow-Up Of Patients With PD
Keywords: Parkinson’s disease; carotid intima media thickness; homocysteine